IoT/cloud‐enabled smart services: A review on QoS requirements in fog environment and a proposed approach based on priority classification technique. (21st November 2019) - Ksentini, Amel; Jebalia, Maha; Tabbane, Sami
Summary: Smart applications are increasingly emerged in our daily professional and personal lives, ranging from augmented reality and gaming applications to E‐health and telesurgery services. In fact, the growing development of Internet of Things (IoT) and its integration with cloud and fog paradigms have encouraged infrastructures and services providers to perform intelligence in advanced technologies. However, the deployment of IoT/cloud‐enabled smart services still suffers from several quality of services (QoSs) management issues such as latency sensitivity for interactive applications and real‐time big data analytics. In this paper, we propose to present a novel approach for the management of smart services QoS. Accordingly, we introduce an overview of QoS requirements in fog computing environment for several IoT/cloud‐enabled use cases, to identify QoS metrics. The synthesis of the requirements review allows us to present a solution for QoS enhancements on the basis of a priority classification (PC) technique. Simulated with iFogSim, PC shows a significant enhancement of the system performance, notably for latency, energy consumption, and network usage. Abstract : In this paper, we propose a novel approach for the management of smart services quality of service (QoS) in fog computing environment. We introduce an overview of QoS requirements for several IoT/cloud‐enabled use cases, to identify QoS metrics. The synthesis of the requirements review allows us to present a solution for QoS enhancements on the basis of a priority classification (PC) technique. Simulated with iFogSim, PC shows a significant enhancement of the system performance, notably for latency, energy consumption, and network usage.